Spatiotemporal variation in mating system and genetic diversity of Araucaria angustifolia: Implications for conservation and seed collection - Stedille L.I.B.* (2021)
© 2020 Elsevier B.V.Understanding spatiotemporal variations in genetic diversity and mating system can allow policymakers to better support actions towards conservation and management of plant populations. However, multiyear studies are still scarce for many long-lived tree species. Therefore, we herein analyze how genetic diversity, genetic structure and mating system of Araucaria angustifolia vary within and among populations, generations (adults and seed cohorts) and years. We evaluated two A. angustifolia populations occurring in forest-grassland landscapes, one of them for three years. Differences in Ho and He were observed among generations and populations, with significant fixation indexes for all adult and seed cohorts evaluated. Pairwise FST values showed that genetic divergences were greater between populations, followed by those among years, and, finally, less relevant values among generations. No significant spatial genetic structure was found in either population. Paternity correlation, number of pollen donors, coancestry and proportion of half and full-sibs may vary over the years in A. angustifolia. In practical terms, the present study demonstrates how recommendations for seed collection may change according to the evaluated year, such as the number of seed trees, which ranged from 42 to 48. Furthermore, multiyear analyses allow a more comprehensive understanding of the genetic aspects for a long-lived tree species. Finally, we present and discuss these aspects and their variations in space, time and between reproductive events, including recommendations for seed collection.